Role of flow experience, recreational participation and place attachment in the socio-economic status of physically active older adults in Tehran province, Iran - Sarbaz, Ali; Seyed Hossini, Rasool Norouzi; Aghaei, Najaf (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
The aim of the current study was to investigate the role of flow experience, recreational participation, and place attachment in the socio-economic status of physically active older adults in Tehran province. This study was a cross-sectional correlational study involving 407 older adults who engaged in sports and physical activity at Velayat Park, Shahr Park, and Niavaran Park in Tehran. Three questionnaires were used to measure the flow experience, place attachment, and socio-economic status, and the data were analyzed using SPSS. There was a significant effect of socio-economic status on flow experience (p < 0.05), while gender did not significantly affect flow experience (p > 0.05). The interaction between gender and socio-economic status did not significantly affect flow experience (p > 0.05). Socio-economic status significantly influenced recreational participation (p < 0.05), and there was a significant gender difference (p < 0.05). The interaction of gender and socio-economic status on recreational participation was significant (p < 0.05). Both socio-economic status (p < 0.05) and gender (p < 0.05) significantly affected place attachment. The interaction of gender and socio-economic status did not significantly affect place attachment (p > 0.05). The findings emphasize the necessity for targeted interventions that consider socio-economic factors to promote positive experiences, participation in recreational activities, and emotional connections among older adults.